Projects of Tourist-Amusement Parks: “Belgrade’s Disneyland” - Jevtović, Aleksandra B. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
Throughout history, the development of entertainment spaces has been intertwined with, and at times even ahead of, changes in the domain of industrial development and modern technologies as well as in the domain of society, urban culture and leisure behavior patterns, driven by both their organizational and aesthetic characteristics. This paper explores key examples of amusement parks that serve as links in the chain of influence and innovation, resulting in the Disney theme parks during the second half of the previous century as a global phenomenon. The focus of the paper is on the presentation and analysis of the amusement park projects in Belgrade designed by architects Aleksandar Đokić and Slobodan Ilić. Those park projects were developed and built during the 1970s and were persistently referred to as “Belgrade’s Disneyland” throughout the planning and construction stages. The aim of the paper is to contextualize the Belgrade project within the broader framework of the cultural and historical development of similar projects worldwide. The results of the paper indicate that Disney’s theme parks played an active role in promoting consumer culture throughout the last century. In Belgrade, however, the construction following a similar model faced social resistance and a series of difficulties during its implementation, which could be interpreted as an example of spontaneous (and short-term) defense of national cultural identity.
Keywords: amusement park; theme park; architecture; tourism; national culture; global culture; Aleksandar Đokić